CONNECTION OF DISEASES OF THE DIGESTIVE SYSTEM WITH STOMOTOLOGICAL DISEASES AND METHODS OF TREATMENT - Tulanova Mokhichehra Akram kizi (Western European Studies, 2024)
In the system of relationships between an internist and other specialists, the aspects of their interaction with a dentist are the least studied. This is primarily due to the isolated structural location of urban and regional dental clinics from other medical institutions. It should be noted the mutual underestimation of changes on the part of organs and tissues of the oral cavity in various diseases of internal organs and under the influence of drug therapy of these diseases.
Keywords: Stomotological diseases; digestive system; dentist